Improving the critical thinking skill through discussion method empowerment by using public controversy text in teaching reading - Yoga Putra Semadi (English, 2021)
This study aims at (1) to find out whether the empowerment of discussion method with public controversy text can improve critical thinking skill in teaching reading and (2) to find out the steps of the empowerment of discussion method with public controversy text to improve critical thinking skill in teaching reading of class X students of SMA Saraswati Singaraja. This research is a Classroom Action-Based Research. The subjects in this study were students of class X.1 SMA Saraswati Singaraja, while the object of this study was the ability to think critically. Data collection methods used were observation and test methods. Before the two cycles were carried out, first the initial test activities were carried out. This pre-test activity aims to determine the initial value of critical thinking skills in reading learning for class X.1 SMA Saraswati Singaraja. The results showed that the empowerment of the discussion method with the use of public controversy texts could improve critical thinking skills in reading learning of students in class X.1 SMA Saraswati Singaraja. Learning is carried out through steps, namely 17 effective learning steps so that they can achieve the learning objectives.